Beyond 'the right to have rights': creating spaces of political resistance protected by human rights. Issue 5 (28th May 2019) - Halper, Jeff; Reifer, Tom
ABSTRACT: What do people do when they are said to 'have rights', but the practice of human rights has been neutralized or indeed inverted by states, depriving them of meaningful protection and the power to actualize them? Beyond offering limited protection and presenting an uplifting vision of what a universal regime of justice might look like, can the human rights regime actually guide movements of fundamental change, or at least help create a critical political space? These are some of the questions raised in this article. Since Israeli impunity towards the human rights regime and the support it receives from governments constitute a major challenge to the efficacy of that regime, and since Israel has pioneered many of the assaults on the global human rights regime, the authors evaluate these questions from the point of view of an Israeli political/human rights organization one of its authors (Halper) heads: the Israeli Committee Against House Demolitions (ICAHD). Given the weakness of human rights implementation, we ask whether grassroots civil society organizations like ICAHD may provide the basis for new global initiatives of rights enforcement from below, and new counter-hegemonic movements to put rights into practice and so help transform the twenty-first-century world-system.